If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) = 2x + -7 Reorder the terms: 3(3 + 2x) = 2x + -7 (3 * 3 + 2x * 3) = 2x + -7 (9 + 6x) = 2x + -7 Reorder the terms: 9 + 6x = -7 + 2x Solving 9 + 6x = -7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 6x + -2x = -7 + 2x + -2x Combine like terms: 6x + -2x = 4x 9 + 4x = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 4x = -7 + 0 9 + 4x = -7 Add '-9' to each side of the equation. 9 + -9 + 4x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = -7 + -9 4x = -7 + -9 Combine like terms: -7 + -9 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 7(4x-6)-7=28x-49 | | ln(x+2)+ln(x+4)=2 | | 3x+5x-4=4 | | 4(5x+6)+2(8-x)= | | 8y+3y+18=2y | | P^2=35+2p | | 106.2+4x=180 | | 11y-6=2y | | -.5*32x^2+24x+50=58 | | -3+5y=17 | | 28.5+.75x=36.75 | | (7xa)x(a-a)-7=56 | | 7(7x-4)+11x= | | 9-74r-7= | | 2m^2+4m-30=0 | | 2(3x+1)+5x(x-2)= | | A^2=a+20 | | 2x^2-15x+35=0 | | 6x+2+2-10= | | -51-5x=75-12x | | 6x+5+5x+3+8x+1=180 | | 19x=41 | | 14=6n+10 | | -(2x-3+4y)= | | -1/5(x-15)-1/9(x-9)=x-3 | | 24x-48=3x^2 | | N^3-4n=32 | | 2/5n-1=15 | | -5x-248=92-15x | | 4(3)x+2=28 | | y=x^11 | | x^3+6x^2+9x=-5 |